2014
DOI: 10.1016/j.addr.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for inhaled drug discovery and development: Induced alveolar macrophage responses

Abstract: Alveolar macrophage (AM) responses are commonly induced in inhalation toxicology studies, typically being observed as an increase in number or a vacuolated 'foamy' morphology. Discriminating between adaptive AM responses and adverse events during nonclinical and clinical development is a major scientific challenge. When measuring and interpreting induced AM responses, an understanding of macrophage biology is essential; this includes 'sub-types' of AMs with different roles in health and disease and mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 149 publications
1
81
0
Order By: Relevance
“…Related to the phenomenon of lung overload in rats, is the effect of poorly soluble drug particles on alveolar macrophage populations. It is has been reported that focal macrophage accumulations often with a "foamy" appearance are a frequent observation in non-clinical toxicology studies of dry powder formulations not only in rats, but non-rodent species as well (Forbes et al, 2014;Lewis et al, 2014). Above certain particle burdens, a progressive neutrophilic inflammation will develop with infiltration of inflammatory cells and elevated pro-inflammatory cytokine production.…”
Section: Toxicology Of Inhaled Biopharmaceuticalsmentioning
confidence: 99%
“…Related to the phenomenon of lung overload in rats, is the effect of poorly soluble drug particles on alveolar macrophage populations. It is has been reported that focal macrophage accumulations often with a "foamy" appearance are a frequent observation in non-clinical toxicology studies of dry powder formulations not only in rats, but non-rodent species as well (Forbes et al, 2014;Lewis et al, 2014). Above certain particle burdens, a progressive neutrophilic inflammation will develop with infiltration of inflammatory cells and elevated pro-inflammatory cytokine production.…”
Section: Toxicology Of Inhaled Biopharmaceuticalsmentioning
confidence: 99%
“…A significant portion of a poorly water soluble inhaled drug is cleared from the central lung by the mucociliary escalator, resulting in a reduced pulmonary bioavailability (27). In the peripheral regions of the lung, clearance by alveolar macrophages dominates, although insoluble particles in the lower airways can give rise to adaptive reversible alveolar macrophage responses, or at higher doses, irreversible alveolar macrophage related adverse events (57). The interplay between dissolution and permeability in the lungs is not well understood, particularly in central regions where low permeation of compounds with low water solubility could result in non-sink conditions for dissolution, making permeation through epithelium the rate-limiting step.…”
Section: Dissolution Permeation Particle Clearance and Tissue Expomentioning
confidence: 99%
“…The aerosol administration of relatively insoluble compounds can result in a dose-dependent, solubilitydependent accumulation of particulate drug material in the lungs [4]. The long-term implications of macrophage responses to drugs of this nature is not completely understood and can be a barrier to the progress of such compounds to clinical development [5]. There are a variety of formulation strategies that may help circumvent the issues of insoluble particle accumulation in the airways, including the loading of agents in lipid nanocapsules [6].…”
Section: Introductionmentioning
confidence: 99%